Final Exam Weighting as Part of Course Design - Matthew Franke (Teaching & Learning Inquiry: The ISSOTL Journal, 2018)
The weighting of a final exam or a final assignment is an essential part of course design that is rarely discussed in pedagogical literature. Depending on the weighting, a final exam or assignment may provide unequal benefits to students depending on their prior performance in the class. Consequently, uncritical grade weighting can discount student learning, by ensuring that improved mastery of material at the semester’s end is not reflected in the course grade. Problems related to several common final exam weights are explored, as are potential solutions to unequal student outcomes made possible by uncritical grade weighting. Ultimately, this essay argues that choosing a weight for a final exam or a final assignment determines what types of student success ought to be possible in the class; therefore, instructors should assign exam weights intentionally, being fully aware of the potential benefits and problems of the weights that they choose.